Forest land-use change affects soil organic carbon in tropical dry forests of the Peruvian Amazon - Vallejos Torres, Geomar; Lozano Chung, Andi; Ordoñez Sanchez, Luis; Garcia Gonzales, Patricia; Gaona Jimenez, Nery; Mendoza Caballero, Wilfredo; Macedo Cordova, Wilder; Saavedra Ramirez , Jorge; Baselly Villanueva, Juan Rodrigo; Marin, Cesar (CSIC (Consejo Superior de Investigaciones Científicas), 2025)
Aim of study: The loss of forest cover is a global problem that alters ecosystems, contributing to carbon emissions. This study measured the soil organic carbon (SOC) at different soil depth in tropical dry forests of the Huallaga Central in the Peruvian Amazon. Area of study: San Martín Region, Peruvian Amazon. Material and methods: A total of 24 plots of 100 m² were selected in primary (~200 years), intervened (~50 years since intervention), and deforested forests (10 years ago), with 120 soil samples collected across five depths. Soil texture (hydrometer), bulk density (cylinder method), SOC content, SOC density, and erodibility (K parameter) were calculated. Main results: SOC content in the 0-20 cm soil horizon was 79.5±21.3 t ha-¹ for the primary forest, 58.5±11.8 t ha-¹ for the intervened forest, and 41.8±10 t ha-¹ for the deforested forest. A soil erodibility K of 0.065 was observed for primary forests and 0.076 and 0.093 for intervened and deforested forests. In average, the SOC density obtained in this study was 7.6±5.1 t ha-¹ in the primary forest, 6.2±3.6 t ha-¹ in the intervened forest, and 4.7±2.7 in the deforested forest. Research highlights: Primary forests had the highest SOC content and SOC density, followed by intervened and deforested forests, while the opposite pattern was found for soil erodibility. These patterns were especially marked in the first 40 cm of soil depth.